Avaliação da melhora da pressão intraocular após injeções intravítreas utilizando manobra de compressão ocular - Carneiro, Lara Pinheiro Maciel (2024)
Intravitreal injections of anti-vascular endothelial growth factor (anti-VEGF) are used in the treatment of several posterior segment diseases characterized by macular edema and/or neovascularization. Although ocular adverse effects from this type of treatment are relatively rare, the main reported effects are: endophthalmitis, cataract progression, vitreous hemorrhage, retinal lesions and elevation of intraocular pressure (IOP). Objectives: To evaluate whether the eye compression maneuver immediately before intravitreal injection is effective in reducing peak intraocular pressure (IOP) after the procedure. Compare the results between the two research groups. Method: A prospective interventional and randomized-controlled clinical study was carried out where 104 eyes of 95 patients were randomized into two groups: in GROUP A, 52 eyes underwent pre-injection eye compression for two minutes, and in GROUP B, 52 eyes received eye compression of the pre-injection for four minutes. After this initial phase of the study, 20 eyes of 20 patients who did not receive pre-injection compression of the eyeball without compression were included (GROUP C).Compression was performed with a cotton swab soaked in OxinestR eye drops (Cristália, Brazil) at the site of application in the superior temporal or nasal quadrant of the eye. An intravitreal injection of anti-VEGF was performed with a standard-recommended volume of 0.05 ml of anti-VEGF medication at the same site as the pre-injection anesthetic compression, using a 30 gauge needle in diameter and 8mm in length via a 3.5mm pars plano route. Posterior to the limbus. All patients underwent IOP measurement with the Goldmann tonometer before the injection and three, 10, 20 and 30 minutes after the procedure. Results: in GROUP A the mean pre-injection IOP was 15.29 mmHg, and the mean IOP after three, 10, 20 and 30 minutes respectively were: 21.77 mmHg, 18.10 mmHg, 15.60 mmHg and 14.52 mmHg. Using the ANOVA method, there was a statistically significant difference between pre-IOP and IOP 3 and 10 minutes after injection (p=0.000). There was no statistically significant difference between the mean pre-IOP and the IOP 20 minutes (p=0.526) and 30 minutes (p=0.101) after the injection. In GROUP B, the mean pre-injection IOP was 15.71 mmHg, and the mean IOP after 3, 10, 20 and 30 minutes respectively were: 20.58 mmHg, 18.62 mmHg, 16.60 mmHg and 16.15 mmHg. There was a statistically significant difference between pre- and post-injection pressures at 3 minutes (p=0.000) and 10 minutes (p=0.000). There was no statistically significant difference comparing each moment between groups A and B. Conclusion: The eye compression maneuver immediately before the intravitreal injection was effective in reducing the IOP peak after the procedure.The results suggest that 2-minute compression is as effective as 4-minute compression in reducing the mean IOP peak after intravitreal injection. Thus, this protocol demonstrated safety and effectiveness in controlling IOP spikes after intravitreal injection.